Fictionality - Petroski, Karen (The New critical idiom, 2023)
Does fiction enhance reality, or threaten our sense of what is real? What, if anything, is special about experiencing fictional works and worlds? Today we speak casually of parallel universes and virtual reality; how much do we really know about what these phenomena involve?